Zinc absorption and zinc status are reduced after either sleeve gastrectomy or Roux-en-Y gastric bypass in premenopausal women with severe obesity studied prospectively over 24 postoperative months. Issue 1 (7th April 2021) - Ruz, Manuel; Carrasco, Fernando; Rojas, Pamela; Codoceo, Juana; Inostroza, Jorge; Basfi-fer, Karen; Csendes, Attila; Papapietro, Karin; Pizarro, Fernando; Olivares, Manuel; Westcott, Jamie L; Hambidge, K Michael; et al.
ABSTRACT: Background: Roux-en-Y gastric bypass (RYGBP) is known to reduce zinc absorption; the effects of vertical sleeve gastrectomy (SG) and its long-term implications on zinc absorption have not yet been studied. Objective: The aim was to evaluate the effects of SG and RYGBP on zinc absorption and zinc status in premenopausal women with severe obesity up to 24 mo after surgery. Methods: Twenty-six premenopausal women undergoing SG [BMI (in kg/m 2 ): 37.3 ± 3.2] and 32 undergoing RYGBP (BMI: 42.0 ± 4.2) were studied. A series of anthropometric, dietary, and zinc status parameters (plasma and hair zinc), and the size of the exchangeable zinc pool (EZP), as well as percentage zinc absorption from a standardized dose using a stable isotope methodology were evaluated in the patients before the surgical procedure and at 12 and 24 mo after SG or RYGBP. SG patients received 15 mg and RYGBP received 25 mg of supplemental Zn/d. Results: In premenopausal women, zinc absorption was decreased by 71.9% and 52.0% in SG and RYGBP, respectively, 24 mo postsurgery, compared with initial values. According to 2-factor repeated-measures ANOVA, time effect was significant ( P = <0.0001), but not time × group interaction ( P = 0.470). Plasma zinc below the cutoff point of 70 µg/dL increased from 0 to 15.4% and 38.1% in SG and RYGBP, respectively. Mean EZP was significantly reduced 24 mo after surgery, although no time × group interactions were observed. Hair zinc did not change across time or between groups. Conclusions: Both SG and RYGBP have profound effects on zinc absorption capacity, which are not compensated for after 24 mo. Although zinc absorption reduction was similar in both types of surgeries, plasma zinc was more affected in RYGBP than SG, despite greater zinc supplementation in RYGBP. This trial was registered at http://www.isrctn.com as ISRCTN31937503.